Hooked : how to build habit-forming products - Eyal, Nir, ....-; Hoover, Ryan, ....- ([North Charleston, S.C.] : [CreateSpace], 2014)
Why do some products capture our attention, while others flop? What makes us engage with certain products out of habit? Is there a pattern underlying how technologies hook us? This book introduces readers to the "Hook Model," a four steps process companies use to build customer habits. Through consecutive hook cycles, successful products reach their ultimate goal of bringing users back repeatedly -- without depending on costly advertising or aggressive messaging.Hooked is a guide to building products people can't put down. Written for product managers, designers, marketers, startup founders, and people eager to learn more about the things that control our behaviors, this book gives readers: - Practical insights to create user habits that stick. - Actionable steps for building products people love. - Behavioral techniques used by Twitter, Instagram, Pinterest, and other habit-forming products.
Includes bibliographical references and Internet addresses.
Keywords: Product design -- Planning; New products -- Psychological aspects; Consumer behavior; Habit